The limits of expertise : rethinking pilot error and the causes of airline accidents - Dismukes, Key (Ashgate studies in human factors for flight operations., 2007)
The Limits of Expertise reports a study of the 19 major U.S. airline accidents from 1991-2000 in which the National Transportation Safety Board (NTSB) found crew error to be a causal factor. Each accident is reported in a separate chapter that examines events and crew actions and explores the cognitive processes in play at each step.